Constructing Another Kind of German: Catholic Commemorations of German Unification in Baden, 1870-1876 - Hiort, Pontus (The catholic historical review, 2007)
This essay discusses how Badenese Catholics responded to the nationalist rhetoric surrounding German unification in 1871. Faced with a Protestant dominated commemorative discourse aimed at reinforcing the Protestant hegemony over the definition of Germanness, Catholics successfully contested this ideological message. By creating an alternative commemorative discourse, Catholics were able to manifest their own understanding of national identity instead of becoming subsumed in a new nation-state based on Protestant values. The uneasy coexistence of Protestant and Catholic versions of German identity suggests that confessional elements constituted integral parts of German nationalism and that Catholic and Protestant integration into the Kaiserreich should be viewed as a contested debate over the definition and legitimization of the new state.